PENGEMBANGAN MODEL KOMPETENSI KEPEMIMPINAN KEPALA RUANG SEBAGAI UPAYA PENINGKATAN MOTIVASI DAN KINERJA PERAWAT PELAKSANA (studi kasus: Rumah Sakit Umum Daerah Kota Mataram, Nusa Tenggara Barat) - PUTU WIDHI SUDARIANI (Universitas Airlangga, 2016)
Introduction: Leadership competencies are unsuitable that given the leadership to employees, can decrease the motivation, performance and ultimately job satisfaction. This research was conducted to develop a leadership competency model as an effort to improve the motivation and performance of nurses so as to improve health services. Methods: This research have two phase, phase one is analytic observational with 140 sample, analysis data with partial least square (PLS), formulation of strategic issues using focus group discussion (FGD), then make a modul with some expertise. Phase two is quasy experimental with 32 sample divided into two group, there are treatment group and control group. Analysis data in phase two with wilcoxon signed rank test and mann whitney. Result and analysis: Phase one there is influence of internal factors (knowledge, skills, and values) to the leadership competencies (t = 3.728> 1.96), there is influence of external factors (cultural organizations) to the leadership competencies (t = 2.257> 1.96), competence leadership influence motivation (t = 3,432> 1,96), leadership competencies influence to performance (t = 2.878> 1.96). The second phase, calculation with Wilcoxon signed rank test showed there is difference motivation in treatment group pre-test and post-test, Mann-Whitney test showed there is influence of development leadership competency model to the motivation of nurses. Test Wilcoxon signed rank test for performance of nurses showed there is difference between pre-test and post-test, Mann-Whitney test was obtained there is influence development of leadership competency model to the performance of nurses. Conclution: Development of leadership competency model can increase the motivation and performance of nurses. Keyword: leadership competences, motivation, performance, nurses ABSTRAK:   Pengantar: Kepemimpinan kompetensi kurang pas yang diberikan pimpinan kepada karyawan, dapat menurunkan motivasi, kinerja dan akhirnya kepuasan kerja. Penelitian ini dilakukan untuk mengembangkan model kompetensi kepemimpinan kepala ruang sebagai upaya peningkatkan motivasi dan kinerja perawat pelaksana sehingga dapat meningkatkan pelayanan kesehatan. Metode: Penelitian ini memiliki dua fase, fase pertama adalah analitik observasional dengan 140 sampel, analisis data dengan parsial least square (PLS), perumusan isu strategis menggunakan focus group discussion (FGD), kemudian membuat modul bersama pakar. Fase kedua adalah quasi eksperimental dengan 32 sampel dibagi menjadi dua kelompok terdiri dari kelompok perlakuan dan kelompok kontrol. Data analisis di tahap kedua ini menggunakan wilcoxon signed rank test dan mann whitney. Hasil dan analisis: Tahap pertama yaitu ada pengaruh signifikan faktor internal (pengetahuan, keterampilan, dan nilai) terhadap kompetensi kepemimpinan (t=3,728>1,96), pengaruh signifikan faktor eksternal (budaya organisasi) terhadap kompetensi kepemimpinan (t=2,257>1,96), Kompetensi kepemimpinan berpengaruh terhadap motivasi (t=3.432>1,96), Kompetensi kepemimpinan berpengaruh terhadap kinerja (t=2,878>1,96). Tahap kedua perhitungan wilcoxon signed rank test pda motivasi menunjukkan ada beda kelompok perlakuan pre-test dan post-test, uji mann-whitney ada pengaruh pengembangan model kompetensi kepemimpinan kepala ruang terhadap motivasi perawat pelaksana. Uji wilcoxon signed rank test kinerja perawat pelaksana menunjukkan ada beda antara pre-test dan post-test, uji mann-whitney diperoleh ada pengaruh pengembangan model kompetensi kepemimpinan kepala ruang terhadap kinerja. Kesimpulan: Pengembangan model kompetensi kepemimpinan dapat meningkatkan motivasi dan kinerja perawat.     Kata kunci: kompetensi kepemimpinan, motivasi, kinerja, perawat